2x2 = 10x + 12 2x2 - 10x - 12 = 0 x2 -5x -6 = 0 x2 - 6x + x - 6 = 0 x(x -6) + 1(x -6) = 0 (x+1)(x-6) = 0 x = -1 or x = 6
46Improved answer:First rearrange this quadratic equation which will have two solutions :2x2-10x-6 = 0Simplify the equation by dividing all terms by 2:x2-5x-3 = 0Then by using the quadratic equation formula it will work out as:x = (5 + the square root of 37)/2or x = (5 - the square root of 37)/2
2x2 + 10x + 25 is a quadratic expression. It describes a parabola.
It is a quadratic equation that has 2 solutions
2x2 + 10 = 9x 2x2 - 9x + 10 = 0 (x - 2)(2x - 5) = 0
2x2 = 10x + 12 2x2 - 10x - 12 = 0 x2 -5x -6 = 0 x2 - 6x + x - 6 = 0 x(x -6) + 1(x -6) = 0 (x+1)(x-6) = 0 x = -1 or x = 6
46Improved answer:First rearrange this quadratic equation which will have two solutions :2x2-10x-6 = 0Simplify the equation by dividing all terms by 2:x2-5x-3 = 0Then by using the quadratic equation formula it will work out as:x = (5 + the square root of 37)/2or x = (5 - the square root of 37)/2
2x2 + 10x + 25 is a quadratic expression. It describes a parabola.
It is a quadratic equation that has 2 solutions
2x2 + 10 = 9x 2x2 - 9x + 10 = 0 (x - 2)(2x - 5) = 0
2x2-10+7 = 0 Solving the quadratic equation using the quadratic formula will give you two solutions and they are: x = (5 - the square root of 11)/2 or x = (5 + the square root of 11)/2
2x2 + 3x - 20 = (x + 4)(2x - 5).
2x2 equals 5
Let P(x) = 2x2 - 10x + 3. Let P(x) = 0, then2x2 - 10x + 3 = 0 (a quadratic equation, where a = 2, b = -10, and c = 3)D = b2 - 4ac = (-10)2 - 4(2)(3) = 100 - 24 = 76
There are no powers e.g 2x2 would be due to the 2
6.50 to the nearest hundredth (4.685 & 1.815)
(-5 plus or minus the square root of 11) divided by 2 x = -0.8416876048223001 x = -4.1583123951777